2020
DOI: 10.1177/2631774520925636
|View full text |Cite
|
Sign up to set email alerts
|

Cap-assisted endoscopic sclerotherapy for internal hemorrhoids: technique protocol and study design for a multi-center randomized controlled trial

Abstract: Background: Cap-assisted endoscopic sclerotherapy is a new interventional therapy for internal hemorrhoids and rectal prolapse under colonoscopy. The proper length of the endoscopic injection needle is the core for performing cap-assisted endoscopic sclerotherapy well with more benefits and less complications. However, no data are currently available to guide endoscopists to consider the length of injection needle before cap-assisted endoscopic sclerotherapy. This study is designed to evaluate the efficacy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…This study evaluated the long-term efficacy and safety of long needle CAES for symptomatic internal hemorrhoids. In Zhang’s et al report[ 5 , 8 , 9 , 16 , 17 ], the follow-up for CAES treatment did not exceed one year. In our study, the time for following CAES treatment was up to 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…This study evaluated the long-term efficacy and safety of long needle CAES for symptomatic internal hemorrhoids. In Zhang’s et al report[ 5 , 8 , 9 , 16 , 17 ], the follow-up for CAES treatment did not exceed one year. In our study, the time for following CAES treatment was up to 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure is typically performed on an outpatient basis and may be repeated as necessary to achieve the desired results. Studies have reported varying success rates of sclerotherapy in treating hemorrhoids, depending on the severity of the condition and other factors [39,40]. However, on average, sclerotherapy has been shown to have a success rate of approximately 70-80% in treating first-and second-degree hemorrhoids.…”
Section: Sclerotherapymentioning
confidence: 99%
“…For patients only with bleeding hemorrhoids, both long and short needles can be selected for injection. [ 4 , 7 ] The long needle is recommended for the hemorrhoids combined with prolapse. The sclerosing agent is injected into the submucosal layer for about 5 s with 0.5 to 2.0 mL lauromacrogol per site.…”
mentioning
confidence: 99%
“…The CAES procedure-associated complications were mainly reported from physicians who were in the early stage of CAES training. [ 7 ] Enema is the way to solve the difficulty in passing gas and defecation, and lower intestinal obstruction. [ 7 ]…”
mentioning
confidence: 99%
See 1 more Smart Citation